The Excavations at Tall Darūk (Usnu?) and 'Arab al-Mulk (Paltos) - Oldenburg, Evelyn (1981)
= Det Kongelige Danske Videnskabernes Selskab, Historisk-filosofiske Skrifter 10:3; p. 83-131 = fig. 1-68; 2 pl.; Usnu, Usana in Assyrian texts from 9th and 8th centuries B.C.; Usnatu in Ugaritic texts.